Hesperidin exacerbates the therapeutic potency of cisplatin against hepatocytotoxicity of Ehrlich ascites carcinoma in mice - Nahed Saleh; Tamer Allam; Reda M. S. Korany; Abdelfattah M. Abdelfattah; Ahmed M. Omran; Mabrouk Attia Abd Eldaim; Nermeen Borai El-Borai (Scientific Reports, 2025)
Abstract The present research was set out to delineate the protective and therapeutic potency of hesperidin (Hesp) versus cisplatin (Cis) against the deleterious consequences of Ehrlich ascites carcinoma (EAC) on the liver and the prospective mitigative effect of Hesp against Cis-mediated hepatotoxic side-effects. A total of 70 female mice were randomly assigned into control, Hesp, EAC, Hesp-protected, Hesp-treated, Cis-treated, and Cis + Hesp-treated groups. Mice inoculated with EAC cells exhibited significant reductions in the serum total protein and albumin levels, along with significant elevations of the serum aminotransferases, lactate dehydrogenase, amylase, and lipase activities, and alpha-fetoprotein level. A significant increment in malondialdehyde level concomitantly with significant declines in reduced glutathione concentration and catalase activity were also observed in the liver of EAC-bearing mice. Additionally, marked hepatic pathological changes as well as a strong Ki-67 expression and a weak caspase-3 expression in the neoplastic cells infiltrating hepatocytes were observed. In contrast, the administration of Hesp and/or Cis to the EAC-bearing mice reversed, to varying degrees, the cytotoxic effects of EAC. Besides, Hesp minimized the harmful hepatic chemotherapeutic side-effects of Cis. Overall, Hesp could be a promising phytochemical against EAC-induced cytotoxicity with its potential to improve the antitumor efficacy of chemotherapeutic drugs and minimize their hepatic adverse side-effects.